2015
DOI: 10.1002/etc.2904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A on antioxidant system in soybean seedling roots

Abstract: Bisphenol A (BPA), an emerging pollutant in the environment, has potential toxic effects on plants. The toxicity mechanism, however, remains largely unknown. The antioxidant system plays an important role in protecting plants against the damage of stress. The present study investigated the effects of BPA on the antioxidant system (superoxide dismutase [SOD], peroxidase [POD], catalase [CAT], ascorbic acid [AsA], proline, reduced glutathione [GSH]), reactive oxygen species (ROS; hydrogen peroxide [H2 O2 ], supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Only a few studies on this joint action have been published for plants, taking into account NPs and heavy metals as occurring contaminants, co-present in the growth medium (Wang et al 2015;Lopez-Luna et al 2016;Ji et al 2017;Rossi et al 2018). Following a specific experimental design, A. filiculoides plants displayed…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies on this joint action have been published for plants, taking into account NPs and heavy metals as occurring contaminants, co-present in the growth medium (Wang et al 2015;Lopez-Luna et al 2016;Ji et al 2017;Rossi et al 2018). Following a specific experimental design, A. filiculoides plants displayed…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, SEM micrographs indicated that BPA exposure markedly decrease the number of open stomata. The reduced number of open stomata may be due to the damaged guard cells, resulting in reduced turgor pressure and ultimately leading to the closure of stomatal pores [6]. The damage to the stomatal aperture can be attributed to increased accumulation of ROS in chloroplasts of stomata.…”
Section: Bpa Exposure Damages Stomata and Guard Cellsmentioning
confidence: 99%
“…Due to its wide use in the production of industrial and household items, the global production of BPA is at an unprecedented high. It has been estimated that the global annual production of BPA is 6.8 million tons [5], and the annual growth rate of demand is 6% to 10% [6]. As a result of its massive usage, BPA has been continuously brought into the environment through industrial waste, sewage sludge, and waste landfill leachate [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations